Pelizaeus-Merzbacher Disease in a 4-Year-Old Female Child: "A Rare Case Report" - Devesh Gagan MBBS, MD Pediatrics; Sudesh Kumar MD Pediatrics; Piyali Bhattacharya MD Pediatrics; Simranjit Kaur MBBS, MD Pediatrics (SAGE Publishing, 2023)
Pelizaeus-Merzbacher disease, a rare X-linked recessive disease occurring predominantly in males, is a disorder of proteolipid protein expression in myelin formation in the central nervous system. The disease is clinically manifested by neurodevelopmental delay, ataxia, hypotonia, and pendular eye movement. It is best confirmed by genetic study. A 4-year female child presented with ataxia, neuroregression, decreased scholastic performance, slurred speech, loss of bladder and bowel control, and hypotonia. MRI brain showed generalized hypomyelination and atrophy of the cerebrum and cerebellum. This case highlights that Pelizaeus-Merzbacher disease can be considered even in a female child who presented with neurodevelopmental delay and neuro regression, ataxia, and decreased scholastic performance and further confirmed by MRI showing diffuse demyelination along with cerebral and cerebellar atrophy.